Maize response to trinexapac-ethyl and nitrogen fertilization Resposta do milho a trinexapac-ethyl e adubação nitrogenada - Durli M.M.* (2020)
© 2020, Sociedade Brasileira da Ciencia das Plantas Daninha. All rights reserved.High nitrogen rates favor maize vegetative growth and grain yield losses due to stem lodging. The use of growth regulators can mitigate such effect. This work was carried out aiming to evaluate the effect of trinexapac ethyl on maize hybrids response to side-dress nitrogen rates. The experiment was carried out in Lages, Santa Catarina State, South of Brazil, during two growing seasons with two hybrids (P1680 and P30F53), and four nitrogen rates (0, 150, 300 and 450 kg N ha-1) were tested, with and without the presence of trinexapac ethyl. The experimental design was in randomized blocks arranged in split-split plots, with three replications per treatment. The plants height and ear insertion height, plant lodging and breaking, grain yield and yield components were evaluated. Grain yield increased in a quadratic way with increased nitrogen rate. The highest grain yields were 15,784 and 15,257 kg ha-1, in 2014/15 and 2015/16, respectively. Application rates higher than 150 kg of N ha-1, regardless of the use of the plant growth regulator, promoted maximum grain yield increases, ranging from 14.7 to 18.1%. The application of trinexapac-ethyl reduced the upper stem internode length, 1000-grain dry weight and did not affect the percentage of lodged plants and grain yield of both hybrids. Therefore, the use of trinexapac-ethyl did not enhance the maize grain yield response to increased rates of side-dress nitrogen.